2017
DOI: 10.1016/j.molimm.2017.06.031
|View full text |Cite
|
Sign up to set email alerts
|

RNAi knock-down of the Bemisia tabaci Toll gene ( BtToll ) increases mortality after challenge with destruxin A

Abstract: Bemisia tabaci (Gennadius) Middle East-Asia Minor 1 (MEAM1) is a well known invasive insect species. Little information is available on immune system of B. tabaci to date. In this study, one of the Toll-like receptors (TLR; namely BtToll) was cloned in MEAM1 B. tabaci which contains an open reading frame of 3153bp, encoding putative 1050 amino acids. Phylogenetic analysis indicated that BtToll is highly identitical with other members of the TLR family. Transcripts of BtToll detected through qRT-PCR were expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…insecticides and pathogens) would be desirable in controlling pests as well as for delaying insecticide resistance development . Silencing of immunity genes, Gram‐negative binding protein 3 and Toll receptor reduced the resistance of the insects to fungal infection . In addition to immunity genes, RNAi mediated knock‐down of a cuticle‐related gene encoding chitin synthase A enhanced the virulence of Beauveria bassiana against Spodoptera exigua .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…insecticides and pathogens) would be desirable in controlling pests as well as for delaying insecticide resistance development . Silencing of immunity genes, Gram‐negative binding protein 3 and Toll receptor reduced the resistance of the insects to fungal infection . In addition to immunity genes, RNAi mediated knock‐down of a cuticle‐related gene encoding chitin synthase A enhanced the virulence of Beauveria bassiana against Spodoptera exigua .…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Silencing of immunity genes, Gram-negative binding protein 3 and Toll receptor reduced the resistance of the insects to fungal infection. 40,41 In addition to immunity genes, RNAi mediated knock-down of a cuticle-related gene encoding chitin synthase A enhanced the virulence of Beauveria bassiana against Spodoptera exigua. 42 As a key factor in cuticle waterproofing, decreased expression of CPs combined with insect pathogen treatment could be important in the integrated population management of aphids.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 represents all target genes from several metabolic pathways of the sweetpotato whitefly including their impact and efficacies that have been evaluated for control. Among them, genes involved in energy metabolism, detoxification, cellular transport and osmoregulation, defense, and metamorphosis have gained the maximum attention of researchers around the globe [ 120 , 121 , 122 , 123 ]. The silencing of genes involved in the regulation of energy metabolism, cellular transport, and osmoregulation has shown mortality of the pest ( Table 4 ).…”
Section: Next-generation Strategies For the Effective Control Of Whitefliesmentioning
confidence: 99%
“…By silencing the TLR in B. tabaci via oral RNAi the efficiency of its immune system could be significantly decreased. Zhang et al () reported that when TLR gene‐specific dsRNA‐treated adults were exposed to a mycotoxin, destruxin A (DA), from the entomogenous fungal strain MZ16 of Metarhizium anisopliae , the toxicity increased by 71% compared with DA treatment only. This study opened the new possibility of managing B. tabaci by weakening its immune system.…”
Section: Microorganism‐mediated Deliverymentioning
confidence: 99%